The latest advancements in Sosuga virus (SOSV) research - Markarian, Nathan M.; Abrahamyan, Levon (Frontiers in Microbiology, 2024)
The last 60 years have seen the emergence of several zoonotic viruses, some of which originate from bats. Among these are Nipah virus, Marburg virus and Ebola viruses, which have high case fatality rates, and pose significant public health risks. In 2012, another zoonotic paramyxovirus from bats, known as Sosuga Virus (SOSV), was discovered in a hospitalized biologist who had returned from a trip to Africa. Given the potential public health threats of the SOSV, investigating its pathogenesis, epidemiology and developing antiviral strategies are crucial to control possible future outbreaks. Thus, in this review, we explore the latest advancements in understanding SOSV since its discovery, focusing on its pathogenesis, animal models and the development of antiviral strategies. By examining the current literature, this review aims to provide a comprehensive overview to guide future studies and help public health efforts in better mitigating potential SOSV outbreaks.